Стратегії брендингу закладів вищої освіти в Україні в умовах демографічної кризи - Харченко, О. С.; Kharchenko, O. S. (Університет економіки і підприємництва, 2025)
Стаття присвячена обґрунтуванню бренд-стратегій українських університетів у демографічній кризі, загостреній після 2022 р. війною й еміграцією молоді. Запропоновано інтегровану модель бренду, що поєднує унікальну ціннісну пропозицію для абітурієнтів, омніканальні цифрові комунікації та довгострокове партнерство з випускниками і роботодавцями. Наукова новизна полягає в узгодженні класифікації бренд-інструментів з адаптованою системою ефективності, яка враховує воєнний контекст та цифрову трансформацію освітнього ринку. Практичне значення полягає у рекомендаціях щодо оптимізації онлайнта офлайн-заходів, підвищення привабливості програм і посилення репутаційного капіталу. Доведено, що гібридні, аналітично обґрунтовані стратегії та міжнародні колаборації стабілізують попит, знижують ризик «провалу набору» і підтримують конкурентоспроможність ЗВО на тривалу перспективу.

The article examines branding strategies for Ukrainian higher education institutions exposed to a prolonged demographic decline intensified by the full-scale war that began in February 2022. The article aims to justify an integrated model enabling universities to maintain enrolment and market relevance despite a shrinking domestic applicant pool. The author systematises existing theoretical approaches to educational branding, analyses institutional marketing constraints, and proposes an original framework that links a clear applicant-oriented value proposition, an omnichannel communication mix, and structured collaboration with graduates and industry. Scientific novelty arises from aligning this framework with a context-sensitive set of effectiveness indicators that reflect wartime disruptions, population displacement, and rapid digital transformation. A mixed-method design was applied: quantitative surveys of senior school students, qualitative interviews with university marketing executives, and monitoring of engagement metrics. The empirical component validates that emphasising practice-oriented curricula, international mobility, and flexible learning formats substantially increases perceived brand attractiveness among prospective students. Practical significance is expressed through guidelines for optimising online and offline recruitment activities, redesigning study programmes to foreground applied learning, and strengthening reputational capital via graduate and employer networks. The conclusions demonstrate that data-driven hybrid strategies – combining storytelling, virtual campus tours, targeted social media campaigns, and evidence-based partnerships – mitigate the risk of severe enrolment decline, stabilise demand for educational services, and sustain institutional viability under crisis conditions. The research highlights the managerial value of tracking brand performance through satisfaction indices, recommendation willingness, and continuous analysis of digital interactions. The findings form a basis for future investigations into the financial returns of branding investment and the ethical implications of personalised communication with applicants, offering a robust starting point for policy and practice in the post-crisis development of Ukrainian higher education.
Branding strategies of higher education institutions in Ukraine under demographic crisis conditions
Keywords: брендінг закладів вищої освіти; демографічна криза; унікальна пропозиція цінності; digital-стратегії; маркетингова аналітика; залучення абітурієнтів; branding of higher education institutions; demographic crisis; unique value proposition; digital strategies; marketing analytics; student recruitment